Aggression and its causes - Renfrew, John W. (Oxford University Press, 1997)
There is also a discussion of the roles that brain mechanisms may play in aggressive behavior, as well as the problems with human brain dysfunction and drug use. The environmental section describes stimuli and environmental conditions that may produce aggression, and the effects of conditioning and learning. Finally, social psychological factors are described, along with the media's effect on aggression. The author covers various applied areas of special contemporary concern, such as juvenile delinquency, sexual and physical abuse of children, spousal abuse, and rape, concluding with a final chapter that discusses various psychiatric disorders that may involve aggression